Confirmation of BD ProbeTec Neisseria gonorrhoeae reactive samples by Gen-Probe APTIMA assays and culture. Issue 1 (1st October 2008) - Hardwick, R; Rao, G Gopal; Mallinson, H
Abstract : Background: Use of nucleic acid amplification tests (NAATs), such as strand displacement assay (SDA), for the detection of gonococcal infection in low prevalence populations is controversial because of the likelihood of false positive results. Use of supplementary NAATs with alternative target sites has been recommended for confirmation of primary NAAT results. Aim: To evaluate if SDA reactive specimens for Neisseria gonorrhoeae, which were either culture positive or negative, can be confirmed by alternative target NAATs such as transcription-mediated assays (TMA). Methods: SDA reactive specimens were retested by TMA using APTIMA Combo 2 (AC2) and APTIMA GC (AGC) assays. Two different methods of specimen preparation were used to test the specimens. In method A, residual extract after SDA was retested and in method B, the original clinical specimen was re-extracted in TMA medium and then retested. Cervical or urethral swabs were requested to confirm the SDA results by culture. Results: By method A, 26/49 (53.1%) of SDA positive specimens were positive by AC2 and/or AGC; 14/27 (51.8%) culture confirmed SDA positive tests were positive by AC2 and/or AGC. By method B, 38/39 (97.3%) SDA positive results were confirmed by both AC2 and AGC. All the 25 culture confirmed SDA positive tests were confirmed by both AC2 and AGC; 5/6 SDA positive tests that were culture negative were confirmed by both AC2 and/AGC. Conclusion: Alternative target site NAATs, such as AC2 and AGC, can be used to confirm SDA positive results using the same clinical specimen. There is high concordance between the three NAATs.